2018
DOI: 10.18805/ijar.b-3469
|View full text |Cite
|
Sign up to set email alerts
|

Gonadal Maturation and Histological observations of S. curvifrons in River Jhelum Kashmir

Abstract: The objective of the present study is to describe the phases of gonadal development and determine the spawning season of Schizothorax curvifrons in River Jhelum Kashmir. A total of 298 fish specimen were studied to analyse the gonadosomatic index and maturity stages of S. curvifrons. Five maturity stages namely Immature phase, Preparatory phase, Maturing phase, Ripe/spawning phase and Spent phase were observed in the gonads. Based on GSI values and gonadal conditions, April to June appears to be the spawning s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…During the current study, S. niger, S. curvifrons, C. diplochilus and G. holbrooki were observed with 'b' value less than 3.0 (b < 3), therefore showing a negative allometric growth pattern. The pattern of negative allometric growth with 'b' value of less than 3.0 has been reported earlier in S. niger (Bashir et al, 2016;Sheikh and Ahmed, 2019), S. curvifrons (Qadri et al, 2017), C. diplochilus (Mushtaq et al, 2016;Sidiq et al, 2021) and in G. holbrooki (Eagderi and Radkhah, 2015). However, C. carpio, C. carassius, P. conchonius showed a positive pattern of allometric growth with b >3.0.…”
Section: Discussionsupporting
confidence: 71%
“…During the current study, S. niger, S. curvifrons, C. diplochilus and G. holbrooki were observed with 'b' value less than 3.0 (b < 3), therefore showing a negative allometric growth pattern. The pattern of negative allometric growth with 'b' value of less than 3.0 has been reported earlier in S. niger (Bashir et al, 2016;Sheikh and Ahmed, 2019), S. curvifrons (Qadri et al, 2017), C. diplochilus (Mushtaq et al, 2016;Sidiq et al, 2021) and in G. holbrooki (Eagderi and Radkhah, 2015). However, C. carpio, C. carassius, P. conchonius showed a positive pattern of allometric growth with b >3.0.…”
Section: Discussionsupporting
confidence: 71%
“…The authors have recently reported uniform spermatogenic capacity in both the principal (September-October) and residual (February-March) breeding seasons in male S. plagiostomus (Purohit et al, 2022). Nonetheless, the seasonal variations in annual ovarian cycle of S. plagiostomus observed were not fully consistent with that reported for other Schizothoracine species found in Kashmir valley, e.g., S. curvifrons (Qadri et al, 2019) andS. niger (FAROOQ et al, 2018) rather differed in terms of time of occurrence and duration.…”
Section: Regressing/spent/post-spawning Stagementioning
confidence: 76%
“…Nonetheless, the seasonal variations in annual ovarian cycle of S. plagiostomus observed were not fully consistent with that reported for other Schizothoracine species found in Kashmir valley, e.g ., S. curvifrons (Qadri et al ., 2019) and S. niger (FAROOQ et al ., 2018) rather differed in terms of time of occurrence and duration. For example, the maturing or developing or pre‐spawning or spawning phase was observed in July–August and September–October in S. plagiostomus , which was found during November–December and March to April for S. curvifrons (Qadri et al ., 2019) and S. labiatus (FAROOQ et al ., 2018), respectively. The spent/regressing/post‐spawning phase was initiated during the onset of winter (November–January) in S. plagiostomus unlike S. labiatus (July–August) (FAROOQ et al ., 2018) and S. curvifrons (May–August) (Qadri et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Morphometric characters considered as measurable structures and are characters describing different external body parts of fish. These characters commonly used in fish biology studies to measure discreteness between different fish stocks (Qadri et al, 2017), and to detect phylogeny of the fish population (Turan, 2004).…”
Section: Introductionmentioning
confidence: 99%